Studi Pemanfaatan dan Peran Masyarakat Lokal terhadap Konservasi Tumbuhan Obat di Desa Cintamanis Baru, Kecamatan Air Kumbang, Banyuasin Sumatera Selatan - Nur Rohmah, Intan Aisyah; Amalia, Imelda Delsy (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Rohmah, N. A. I., & Amalia, D. I. (2024). Utilization study and the role of local people to the medical plants conservation at Cintamanis Baru Village, Air Kumbang District, Banyuasin, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 490–500). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Indonesia is known as a country with sources of medicinal raw materials from tropical plants that can treat various diseases. The use of plants as medicines has also been known and utilized since long ago by the community. However, the knowledge and sustainability of medicinal plants in Indonesia are potentially extinct along with the continued existence of life, increased environmental degradation, and utilization that has not been well documented. Farming traditions in rural communities play a key role in conserving medicinal plants and preserving knowledge for future generations. The study aims to identify the role of local communities in conserving medicinal plants based on their knowledge and use. The research was conducted in September 2024 in Cintamanis Baru Village, Air Kumbang Subdistrict, Banyuasin Regency, South Sumatra, which includes 4 hamlets.The research method is qualitative descriptive. Data were obtained by direct observation and interviews based on structured questionnaires to 20 respondents. The results revealed 25 families of 43 medicinal plant species, primarily Zingiberaceae (12%) and herbaceous plants (46%), cultivated by the community to treat various diseases, with Javanese ethnicity being the most represented (75%), followed by Balinese and Sundanese. The level of knowledge and utilization is higher among women (80%) who are married (60%) and unmarried (25%). Local people's close relationship with medicinal plants comes from sources of knowledge obtained from parents (90%) and the internet (10%) with a duration of 10-25 years during their lifetime. The close relationship shows that local people have a very important role in the sustainability of medicinal plant conservation.